(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
Swift system comprises and excellent example of unification and standardization to boost efficiency and reliability of banking operations. On this basis, the most frequent incorrect operations have been analyzed and clear advice on how to boost the banking efficiency have been examined. In order to boost banking effectiveness, the elimination of the mistakes mentioned above is of paramount importance.